Hubungan Indeks Massa Tubuh dengan Tekanan Darah Sistolik pada Pasien Penyakit Ginjal Kronik yang Menjalani Hemodialisis di RSUD dr. Zainoel Abidin - Sitti Maziyyah Aini; Novita .; M. Darma Muda Setia (Jurnal Ilmiah Mahasiswa Kedokteran Medisia, 2017)
Higher blood pressure can increase the mortality of patients with Chronic Kidney Disease (CKD) when undergoing Hemodialysis (HD). Body Mass Index (BMI) is one of the factors that may increase the patient’s blood pressure. This type of research was analytic study with cross sectional design. The sample in this study were the patients who undergo HD for at least 3 months and  that were taken by total sampling as many as 46 patients. The data were taken from the patient’s weight using digital chairs scales, height data using the stature meter and blood pressure data using mercury sphigmomanometer and stethoscope. Data were collected after patients doing HD. Patients consisted of 30 male patients (65,2%) and 16 female patients (34,8%). Based on the BMI, the measurements were divided into three categories, which were overweight, normal and underweight. The result of the measurements were 5 patients of overweight category (10,9%), 31 patients of normal category (67,4%), and 10 patients of underweight category (21,7%). Based on the systolic blood pressure measurement post dialysis, there were 32 patients (69,6%) with hypertension and 14 patients (30,4%) with normal blood pressure. By using the Spearman test, there were no influence between BMI with systolic blood pressure (p 0,953 p0,05 r 0,009). It was concluded that there were no relation between BMI and the systolic blood pressure